A comparative clinical evaluation of outcome of medical and surgical management of symptoms due to benign prostatic hyperplasia - Gnana, Bhushan Kumar; Matlapudi, Sanjeeva Rao (International Surgery Journal, 2020)
Background: Benign hypertrophy of prostate is common disorder and benign neoplasm of man above 50 years of age. Around 30% patients with benign hypertrophy of prostate lower urinary tract symptoms (LUTS) but all symptoms may not be due to benign hypertrophy of prostate (BHP). Present study has been designed for comparative evaluation of the outcome of medical and surgical management of symptoms, due to benign prostatic hyperplasia by using IPSS (international prostate score) and quality of life score as tool. Methods: In present study patients with LUTS, clinically diagnosed by per rectal digital examination and transrectal ultrasonographically confirmed cases of enlargement of prostate are enrolled for this study. Patients enrolled were divided equally in three groups. Results: After six month the mean IPSS score in silodosin (Sd) group was 6.55±0.86 and in Sd+Dutasteride (Dt) group it was 5.09±1.12. After six months mean IPSS score in Sd+Dt group was 5.09±1.12 and in TURP group it was 2.44±0.59. Conclusions: Single drug treatment with silodosin is associated with slow and less improvement in IPSS score in comparison with silodosin and dutasteride. But the response to TURP was better and faster than medical management.